Engaging heritage, engaging communities - Onciul, Bryony; Stefano, Michelle L.; Hawke, Stephanie Kate (Woodbridge, Suffolk : The Boydell Press, 2017)
Across the global networks of heritage sites, museums, and galleries, the importance of communities to the interpretation and conservation of heritage is increasingly being recognised. Yet the very term "meaningful community engagement" betrays a myriad of contrary approaches and understandings. Who is a community? How can they engage with heritage and why would they want to? How do communities and heritage professionals perceive one another? What does it mean to "engage"? These questions unsettle the very foundations of community engagement and indicate a need to unpick this important but complex trend. This book critically explores the latest debates and practices surrounding community collaboration. By examining the different ways in which communities participate in heritage projects, the book questions the benefits, costs and limitations of community engagement. Whether communities are engaging through innovative initiatives or in response to economic, political or social factors, there is a need to understand how such engagements are conceptualised, facilitated and experienced by both the organisations and the communities involved.
Machine generated contents note: Engaging Concepts -- 1.The Gate in the Wall: Beyond Happiness-making in Museums / Bernadette Lynch -- 2.Assembling Communities: Curatorial Practices, Material Cultures and Meanings / Philipp Schorch -- 3.Interview / John Tunbridge -- 4.Interview / Gregory Ashworth -- 5.Engaging with Maori and Archaeologists: Heritage Theory and Practice in Aotearoa New Zealand / Elizabeth Pishief -- 6.Horizontality: Tactical Politics for Participation and Museums / Helen Graham -- Engaging Creatively -- 7.Re-imagining Egypt: Artefacts, Contemporary Art and Community Engagement in the Museum / Gemma Tully -- 8.Interview / Evita Busa -- 9.Interview / Shatha Abu Khafajah -- 10.Engaging Communities of De-industrialisation: the Mapping Baybrook and Mill Stories Projects of Baltimore, USA / Nicole King -- 11.Interview / Ashley Minner -- Engaging Challenges -- 12.Embattled Legacies: Challenges in Community Engagement at Historic Battlefields in the UK / Justin Sikora -- 13.At the Community Level: Intangible Cultural Heritage as Naturally-occurring Ecomuseums / Michelle L. Stefano -- 14.Subaltern Sport Heritage / Gregory Ramshaw -- 15.Museums and the Symbolic Capital of Social Media Space / Julian Hartley -- 16.Relational Systems and Ancient Futures: Co-creating a Digital Contact Network in Theory and Practice / Wayne Ngata -- 17.Interview / Conal McCarthy.
"The International Centre for Cultural & Heritage Studies, Newcastle University"--Cover.
Includes bibliographical references and index.
Keywords: Museums -- Management; Museums and community; Historic sites -- Management; Community archaeology; Community archaeology; Historic sites -- Management; Museums and community; Museums -- Management; 20.12 art museums